Development of a remote analysis method for underground ventilation systems using tracer gas and CFD in a simplified laboratory apparatus - Xu, Guang; Luxbacher, Kray; Ragab, Saad; Schafrik, Steve (Pergamon, 2013)
Following a disaster in a mine, it is important to understand the state of the mine damage immediately with limited information to manage the emergency effectively. Tracer gas technology can be used to understand the ventilation state remotely where other techniques are not practical. Computational fluid dynamics is capable of simulating and ascertaining information about the state of ventilation controls inside a mine by simulating the airflow and tracer distribution. This paper describes a simulation of tracer gas distribution in a simplified laboratory experimental mine with the ventilation controls in various states. Tracer gas measurements were taken in the laboratory experimental apparatus, and used to validate the numerical model. The distribution of the tracer gas, together with the ventilation status, was analyzed to understand how the damage to the ventilation system related to the distribution of tracer gases. Detailed error analysis was performed and the discrepancies between experimental and simulated results were discussed. The results indicate that the methodology established in this study is feasible to determine general ventilation status after incidents and can be transferred to field experiment. Because it is complex to simulate the actual condition of an underground mine in a laboratory, the model mine used is simplified to simulate the general behavior of ventilation in a mine. This work will be used to inform planned on-site experiments in the future and the proposed methodology will be used to compare collected and simulated profiles and determine the general location of ventilation damage at the mine scale.